The Importance of Building Religious Tolerance In Indonesia Through Multicultural Education From An Islamic Perspective - Putri, Anggi Ariska; Nurhuda, Abid; Assajad, Anas; Sinta, Dewi (UAS PRESS, 2024)
Indonesia is a diverse archipelagic country where it holds uniqueness in every corner. Uniting diversity is not an easy thing even though the majority of the community is Muslim but religious conflicts still often occur due to a lack of tolerance towards other people. So the purpose of this study is to describe the Importance of Building Religious Tolerance in Indonesia Through Multicultural Education in an Islamic Perspective. The method used is qualitative with a literature study approach, then the data are collected both primary and secondary by careful observation techniques, then analyzed, and finally concluded descriptively. The results of the study show that the Importance of Building Religious Tolerance in Indonesia Through Multicultural Education from an Islamic Perspective is to be able to build an inclusive religious and diversity paradigm, followed by respecting the diversity of cultures, languages, ethnicities, races, and religions. And the last is to build a gender-sensitive attitude. These three things in Islam are under the principles of maqosidu sharia, one of which is closely related to ad-din/religion.